Species diversity of the Genus Hoya (Asclepiadaceae) in Bukit Batikap Sanctuary Forest, Central Kalimantan - SRI RAHAYU (Biodiversitas Journal of Biological Diversity, 2006)
The Genus Hoya (Apocynaceae: Asclepiadoideae) is being appreciated as exotic ornamental plant in Europe, USA and Australia, while in Indonesia as the country of origin still neglected. Indonesia was predicted have the highest Hoya species diversity (about 60 species from 150 species in the world). Among the major Islands in Indonesia, Kalimantan was predicted have the highest diversity in Hoya species. The inventory of the species has been done in the Bukit Batikap Sanctuary Forest, Muller Mountain in Central Kalimantan. Nine Hoya species of about thirties species in Kalimantan were found in Bukit Batikap, namely: H. coronaria Blume, H. cf. erythrostemma Kerr., H. latifolia G. Don., H. mitrata Kerr., H. nummularioides Const., H. pusilla Rintz, H. revoluta Wight, H. scortechinii King & Gamble, and Hoya cf. vaccinioides Hook.f. Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: Hoya, diversity, Bukit Batikap, Muller Mountain, Kalimantan